High‐Precision Fe and Mg Isotope Ratios of Silicate Reference Glasses Determined In Situ by Femtosecond LA‐MC‐ICP‐MS and by Solution Nebulisation MC‐ICP‐MS. Issue 3 (7th August 2014) - Oeser, Martin; Weyer, Stefan; Horn, Ingo; Schuth, Stephan
<x xml:space="preserve">Abstract</x> In this study, a technique for high precision in situ Fe and Mg isotope determinations by femtosecond‐laser ablation‐multi collector‐ICP‐MS (fs‐LA‐MC‐ICP‐MS) was developed. This technique was employed to determine reference values for a series of common reference glasses that may be used for external standardisation of in situ Fe and Mg isotope determinations in silicates. The analysed glasses are part of the MPI‐DING and United States Geological Survey (USGS) reference glass series, consisting of basaltic (BIR‐1G, BCR‐2G, BHVO‐2G, KL2‐G, ML3B‐G) and komatiitic (GOR128‐G and GOR132‐G) compositions. Their Fe and Mg isotope compositions were determined by in situ fs‐LA‐MC‐ICP‐MS and by conventional solution nebulisation multi‐collector ICP‐MS. We determined δ56Fe values for these glasses ranging between ‐0.04‰ and 0.10‰ (relative to IRMM‐014) and δ26Mg values ranging between ‐0.40‰ and ‐0.15‰ (relative to DSM‐3). Our fs‐LA‐MC‐ICP‐MS results for both Fe and Mg isotope compositions agreed with solution nebulisation analyses within analytical uncertainties. Furthermore, the results of three USGS reference glasses (BIR‐1G, BHVO‐2G and BCR‐2G) agreed with previous results for powdered and dissolved aliquots of the same reference materials. Measurement reproducibilities of the in situ determinations of δ56Fe and δ26Mg values were usually better than 0.12‰ and 0.13‰ (2s), respectively. We further demonstrate that our technique is a suitable tool to resolve isotopic zoning in chemically‐zoned olivine crystals. It may be used for a variety of different applications on isotopically‐zoned minerals, e.g., in magmatic or metamorphic rocks or meteorites, to unravel their formation or cooling rates.